The limitations of mouth alcohol detection systems in breath alcohol testing: Case reports - Aaron Olson (Forensic Science International: Synergy)
Contamination of a person's breath alcohol with alcohol from sources other than the lungs can falsely elevate the results of a breath alcohol test. This is known as “mouth alcohol” contamination in breath alcohol testing. To combat the issue of mouth alcohol contamination, manufacturers of breath alcohol analyzers have incorporated slope detection algorithms into their devices known as “slope detectors.” Despite this effort, breath alcohol analyzers sometimes fail to detect mouth alcohol contamination. Three case reports presented in this paper strongly suggest undetected mouth alcohol contamination. The significant legal consequences of a falsely elevated breath alcohol concentration (BrAC) due to mouth alcohol contamination require further research into the ability of slope detectors to identify mouth alcohol. Greater transparency and independent scientific examination of the algorithms involved in mouth alcohol detection systems are needed to ensure accuracy and fairness in breath alcohol testing.